Biomechanical analysis of two standing sprint start techniques - LeDune, J. A.; Nesser, T. W.; Finch, A.; Zakrajsek, R. A. (The Journal of Strength and Conditioning Research, 2012)
The purpose of this study was to examine any differences between the false step standing sprint start and a traditional forward step standing sprint start. Ten DI collegiate female soccer players performed 2 standing sprint starts (Forward step and False step). Each player was videotaped for the first 3 steps of each sprint start. Velocity, acceleration, and displacement were calculated at each of the 3 steps for both standing sprint start techniques. Velocity was significantly faster with the forward step for steps 1 and 2 but not with step 3. Displacement was significantly greater with the forward step for each of the 3 steps. Acceleration was greater with the false step for each step though differences were not significant. The results indicate the forward step outperforms the false step in both velocity and displacement. Even though the false step generates greater acceleration, the backward step drastically undercuts displacement nullifying acceleration. Controversy exists between these 2 standing sprint starts with proponents arguing for their favorite with no evidence to suggest one or the other. The results from this study suggest that the forward step is superior to the false step when the concern for an individual is to get from 1 point to the next as fast as possible.